Photon-Induced Hot Electron Effect on the Catalytic Activity of Ceria-Supported Gold Nanoparticles - Kim, Sun Mi; Lee, Hyosun; Goddeti, Kalyan C.; Kim, Sang Hoon; Park, Jeong Young (American Chemical Society, 2015)
The role of charge transfer at the metaloxide interface is a long-standing issue in surface chemistry and heterogeneous catalysis. Previous studies have shown that the flow of hot electrons crossing metaloxide interfaces correlates with catalytic activity. In this study, we employed ceria-supported gold nanoparticles to identify a correlation between the catalytic activity of CO oxidation and hot electrons generated via light irradiation. We tuned the size of the Au nanoparticles by changing the discharge voltages used in the arc plasma deposition process, thus allowing us to investigate the influence of Au nanoparticle size on changes in catalytic activity. CO oxidation over the Au/CeOX catalysts was carried out, and we found that the activity of the Au nanoparticles increased as the size of the nanoparticles decreased, which is associated with the cationic character of the Au nanoparticles, as demonstrated by X-ray photoelectron spectroscopy analysis. We also show that the activity of the Au nanoparticles decreases under light irradiation and that smaller nanoparticles show a higher change of turnover frequency compared with larger ones, presumably due to the mean free path of the hot electrons. From these results, we conclude that the cationic property of the gold species, induced by interaction with the CeO2 support, and the flow of hot electrons generated on the interface during light irradiation are mainly responsible for the change in catalytic activity on the Au nanoparticles.
Keywords: LOW-TEMPERATURE OXIDATION; CO OXIDATION; AU/CEO2 CATALYSTS; AU; PLATINUM; HYDROGEN; SURFACE; REACTIVITY; MECHANISM; CATIONS